The Influence of Leader-Member Exchange and Mindfulness on Work Engagement at PT Great Giant Pineapple - Paramesthi, Gading Azarine; Ribhan, Ribhan (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study aims to examine the direct influence of leader-member exchange and mindfulness on work engagement in permanent employees in the farming service department of PT Great Giant Pineapple. The research was conducted using a quantitative approach with data collection using a questionnaire with a Likert scale. The sampling method used probability sampling with simple random sampling technique, with a sample size of 180 respondents. Instruments, hypothesis testing, and research data were analyzed using SPSS 26 software. This research analysis method uses multiple regression analysis. The results showed that this study supports all hypotheses, leader-member exchange has a direct positive and significant effect on work engagement, and mindfulness has a direct positive and significant effect on work engagement, based on the research that has been done, indicating that companies need to develop mutually supportive relationships based on trust to encourage strong work engagement. Increasing mindfulness in individuals can help employees work multitasking, because it can build a higher level of vitality in work activities, then in an effort to maintain strong work engagement, companies should provide creative challenges and innovations in work tasks.